Effect of bonded composite patch on the stress intensity factor for a center cracked plate - Aabid, Abdul; Hrairi, Meftah; Syed Mohamed Ali, Jaffar; Abuzaid, Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Crack propagation until fracture is an important criterion to predict a structure‘s service life. In order to increase the latter, the cracked component needs to be repaired or replaced. In the present study, a finite element analysis has been carried out to investigate the effects of adhesive thickness, patch thickness and crack length on the passive repair performance of a center-cracked rectangular aluminum plate under mode-I loading condition using an ANSYS package. A comprehensive parametric study shows that the stress intensity factor is influenced by the patch thickness, patch size, adhesive material, and adhesive thickness. **************************************************************************** Penyebaran retak sehingga patah adalah kriteria penting bagi menjangka hayat struktur. Bagi memanjangkan jangka hayat struktur, komponen keretakan perlu dibaik pulih atau diganti. Kajian ini telah menjalankan analisis elemen tak terhingga bagi mengetahui kesan ketebalan pelekat, ketebalan tampalan dan panjang retak pada bahagian keretakan tengah plat petak aluminium yang dibaiki secara pasif, menggunakan pakej ANSYS di bawah beban mod-I. Kajian parametrik yang menyeluruh menunjukkan faktor tekanan intensif dipengaruhi oleh ketebalan tampalan, saiz tampalan, bahan pelekat dan ketebalan pelekat.